The Network Formation Origin of Tribal Societies (2018)
This paper proposes a network formation model for explaining the stability of tribal societies. The model is supported by the idea that every two members of a tribe should have benefited from being connected to each other in order for the whole tribe to be stable. It also considers the constraints that the ecosystem brought to social interaction in pre-modern contexts. The model has three predictions. First, both homogeneous and heterogeneous tribes could have been stable regardless of technological development. Second, the social complexity of tribes was a function of technological development (having access to agriculture should have enabled the emergence of larger and more complex societies), interaction costs (if they were too low or too high, no complex society should have emerged), and environmental conditions (poor ecosystems should not have allowed the formation of complex societies). Finally, the model predicts that collapses of agricultural societies could not come from environmental pressures, but from high interaction costs. The predictions are consistent with some of the most relevant human history patterns